BIODEGRADATION OF PERMETHRIN PESTICIDE BY USING Brevibacillus brevis RCGM1 - R. S. CHAVAN; G. V. MALI; B. K. Bhavikatti; A. S. PAWAR (The Bioscan, 2026)
The high application of the permethrin pesticide in modern agriculture has resulted in their retention in the soil matrices making them a great threat to soil biodiversity and non-target organisms. Microbial biodegradation has been considered an economical and ecologically safe substitute to the traditional remedial processes. Soil samples enriched with permethrin were used in the current study to enrich putative pesticide degrading bacterial strains. A strain was identified as Brevibacillus brevis RCGM1 by the means of 16S rRNA gene sequencing with 97% sequence similarity and was successfully isolated and taxonomically identified. The isolate revealed the ability to use permethrin as the only carbon and nitrogen source and showed resistance to the high concentration of pesticides. The efficiency of degradation was 84.48% in eight days, which was proved by UV- Vis spectrophotometric analysis. Fourier -transform infrared spectroscopy (FTIR) revealed a structural change of the compound, which indicated the cleavage of ester bonds, and Gc-MS confirmed that the metabolites were converted to ester hydrolysis and further oxidation to 3 -phenoxybenzoic acid and phenol. These results highlight the biodegradation capability of Brevibacillus brevis RCGM1 and indicate a promising future in their use in the bioremediation of pesticide contaminated soils, hence sustainable production and soil remediation. Keywords Permethrin, Biodegradation, Brevibacillus brevis RCGM1, FTIR, GCMS.